Educação e linguagem : em busca do conceito de enunciação em referenciais curriculares de língua portuguesa - Zanette, Carla Roberta Sasset (My University, 2016)
This research investigates the concept of enunciation, from Émile Benveniste’s theoretical perspective, and those that constitute it (I-you-here-now) in the document entitled Referenciais da Educação da Rede Municipal de Caxias do Sul (Education Framework for the Municipal Schools in Caxias do Sul). The research focuses more specifically on the general goals and skills of the 7th and 9th school years found in the number 2 Study Plan booklet for the Portuguese Language. The study is essentially bibliographic and is based on Saussure’s and Benveniste’s views as well as on other researchers whose works are related to education, epistemology, the teaching and learning processes and to issues on the mother tongue. The effective analysis of the enunciation concept is carried out based on a theoretical material framed according to a reading program. This material consists of six essays found in the two volumes of Problems in General Linguistics by Benveniste: the nature of the linguistic sign (1939), the nature of pronouns (1956) and subjectivity in language (1958); language and human experience (1965), form and meaning in language (1966/1967) and the formal apparatus of enunciation (1970). Based on the results presented in this study, I understand that the planning of the analyzed material, considering both the general goals and the skills, materializes the concept of enunciation and those that constitute it. The results show that the teaching of the mother tongue is based on an enunciative perspective, which considers the effective use of language in many different situations of interlocution.
A partir de pressupostos teóricos de Émile Benveniste, esta pesquisa investiga o conceito de enunciação e os que o constituem (eu-tu-aqui-agora), no documento intitulado Referenciais da Educação da Rede Municipal de Caxias do Sul, Caderno 2 - Planos de Estudo de Língua Portuguesa, mais especificamente, no que diz respeito aos objetivos gerais e às habilidades dos 7° e 9° anos. De cunho essencialmente bibliográfico, esta investigação fundamenta-se em referenciais teóricos de Saussure e Benveniste, entre outros autores que tratam de educação, epistemologia, processos de ensino e aprendizagem e de questões relacionadas à língua materna. A análise efetiva do conceito de enunciação é realizada com base em um material teórico delimitado a partir de um itinerário de leitura. Esse material é composto por seis textos das obras benvenistianas Problemas de Lingüística Geral I e II: Natureza do signo linguístico (1939), A Natureza dos pronomes (1956) e Da subjetividade na linguagem (1958); A linguagem e experiência humana (1965), A forma e o sentido na linguagem (1966/1967) e O aparelho formal da enunciação (1970). Com base nos resultados apresentados neste estudo, entendo que a organização do material analisado, seja pelos objetivos gerais, seja pelas habilidades, concretiza o conceito de enunciação e os que o compõem, evidenciando o ensino de língua materna, sob uma perspectiva enunciativa, que considera o efetivo uso da língua, nas mais diferentes situações interlocutivas.
Keywords: Benveniste, Emile, 1902-1976; Saussure, Ferdinand de, 1857-1913; Aprendizagem; Educação - Estudo e ensino; Língua portuguesa - Estudo e ensino; Learning; Education - Study and teaching; Portuguese language - Study and teaching